Strategic objectives for job creation in Ecuador - Andrade Romero, Mauro; Andrade Merino, Raúl; Slusarczyk Antosz, Maria; Andrade Montalvo, Felipe (mktDESCUBRE; Vol 1 No 20 (2022): Twentieth Edition (July - December), 2022)
The creation of employment in Ecuador, after the first great depression of the 21st century, has been complicated due to the lack of public policies, and the participation of the state as part of the generation of employment, in a community without liquidity, with a strong GDP contraction, job cuts, with a total absence of public policies aimed at supporting the maintenance of employment, the increase in poverty levels, among others; they are signs of a weak economy torn between poverty and inequality. The purpose of this research work is to propose strategic alternatives for public policies and financial instruments that mitigate the destruction of employment, helping 70% of the Economically Active Population (EAP) that is unemployed. To achieve this goal, we perform an analysis of the behavior of the prevailing financial economic variables in the environment.